2022
DOI: 10.1002/acr.24529
|View full text |Cite
|
Sign up to set email alerts
|

Children With Enthesitis‐Related Arthritis and Possible Benefits From Treatments for Adults With Spondyloarthritis

Abstract: This review will summarize clinical, genetic, and pathophysiologic characteristics that are shared between children with enthesitis‐related arthritis (ERA) with axial involvement and adults with nonradiographic (and in some cases radiographic) axial spondyloarthritis (SpA), as well as between children with ERA and primarily peripheral disease manifestations and adults with peripheral SpA. Due to the differences in classification criteria for children with ERA and adults with axial and peripheral SpA, the US Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The responses in children with JPsA receiving secukinumab in this study are consistent with the findings from studies in patients with PsA where secukinumab has demonstrated sustained improvements in ACR responses, in resolution of enthesitis and dactylitis, in skin clearance with sustained improvement across the six key manifestations of PsA through 5 years. 24–26 ERA is considered the paediatric counterpart of nr-axSpA 2 and children with ERA also experienced a profound improvement of signs and symptoms of their disease. The role of IL-17A in spondyloarthritide manifestations of skin, joints and entheses is well known, and profound improvement with secukinumab was reported in patients with PsO, PsA and AS.…”
Section: Discussionmentioning
confidence: 99%
“…The responses in children with JPsA receiving secukinumab in this study are consistent with the findings from studies in patients with PsA where secukinumab has demonstrated sustained improvements in ACR responses, in resolution of enthesitis and dactylitis, in skin clearance with sustained improvement across the six key manifestations of PsA through 5 years. 24–26 ERA is considered the paediatric counterpart of nr-axSpA 2 and children with ERA also experienced a profound improvement of signs and symptoms of their disease. The role of IL-17A in spondyloarthritide manifestations of skin, joints and entheses is well known, and profound improvement with secukinumab was reported in patients with PsO, PsA and AS.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ILAR criteria, JIA is divided into seven mutually exclusive subgroups and ERA is one of the most controversial subtypes of JIA, which differ from other types of inflammatory arthritis in genetic predisposition, pathogenesis, and risk of axial involvement [7]. Since the studies specifically performed on ERA are limited, the knowledge regarding ERA is based mainly on data from adults with spondyloarthritis (SpA) [8]. The largest study, which included 312 ERA patients, was reported from northern India in 2016 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all our patients with axial involvement needed anti-TNF treatment. Since ERA patients tend to have higher disease activity, and risk of axial involvement, the treatment of ERA should be more aggressive than other subtypes of JIA [3,8]. Previous studies have clearly shown that methotrexate alone is not an effective treatment in adult SpA [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive arthritis, IBD-related arthritis, and psoriatic arthritis are not among the diagnostic criteria in ERA. While psoriatic arthritis in children is a different subgroup of JIA, both psoriatic arthritis, reactive arthritis, and IBD are included in the SpA group in adults (23). Secondly, the ILAR classification criteria focus on the importance of extra-axial manifestations such as peripheral arthritis and enthesitis, while SpA classification pays attention to the presence of axial and spinal involvement.…”
Section: Classification Criteriamentioning
confidence: 99%